Differential-geometric structures in operads - Daletskii, Yu. L. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We describe certain structures of formal differential geometry in terms of the theory of operads and introduce group structures, Lie-algebra structures, exponential mappings, and an analog of the de Rham complex.